Geographical distribution of fire accidents in the holy city of Najaf and ways to reduce them - Al-Abdali, Rahim Mohammed Abid Zaid (Al-Adab Journal, 2019)
Civil defense is one of the most important governmental institutions and great hopes that are attached to all sectors of society. The society is eager for security based on new responsibilities dictated by the circumstances of the times, its changes, developments and repercussions. The search problem was as follows What is the general trend of temporary and spatial fire accidents in Najaf city and What is the relationship between the development and location of the civil defense teams and the number of incidents in the city of Najaf. The research discussed the general concepts included in the research as well as the spatial distribution of fires in the city of Najaf and then their temporal distribution to go to the time of fire and to indicate the physical damage to the fires in the city as well as the study of the situation of civil defense and clarify the points of the presence of Mraz to end the study study of the proposed places according to the criterion of spatial and numerical revival Residential results were the most prominent. The increase in the number of fires in the province due to the increase in the population and the number of arrivals and due to the nature of the tourist and religious province and the large commercial activity, industrial, residential and agricultural. By looking at the means of implementation and treatment, there is a clear lack of the number of civil defense centers in the city of Najaf. The main reason for the occurrence of accidents in all sites (governmental and private sector) is the main reason for the occurrence of accidents.